Nanocomposites materials generated from a spray - Marques, Rodrigo Fernando Costa [UNESP]; Caiut, J. M. A. [UNESP]; Paiva-Santos, C. O. [UNESP]; Ribeiro, Sidney José Lima [UNESP]; Messaddeq, Younes [UNESP]; Garcia, C.; Neumeyer, D.; Dexpert, H.; Verelst, M.; Dexpert-Ghys, J. (Sociedade Brasileira de Física, 2009)
The Spray Pyrolysis (SP) process has been employed at moderate temperature (470-970 K) for the synthesis of micro- and nano-particles of hydrated metal oxides and of related nanocomposites. It has been applied to iron nitrate solutions, without or with the addition of sodium chloride as a flux. After removal of the flux, nanocomposites of ferrihydrite (5Fe2O3,9H2O) / hematite (α- Fe2O3) / and an amorphous Fe2O3 are obtained, with surface area 140 m²/g. It has been applied also to a sol of Aluminum-tri-sec-butoxide, without or with activation by europium or terbium ions. Boehmite (γ-AlOOH) powders are synthesized at 470 K, with surface area equal to 180 m²/g. Transition alumina (γ-Al2O3) are synthesized at 970 K. Nanocomposites made by reaction of the boehmite or γ-Al2O3 particles with the amino acid asparagin (ASN) have been prepared and characterized. The luminescence of the Eu3+ or Tb3+ doped nanocomposites has been investigated: they can be considered as bio-compatible luminescent nanoparticles.
Keywords: Spray-pyrolysis; Nano-powders; Ferrihydrite; Hematite; Boehmite; Alumina